The leadership crisis and the free market cure why the future of business depends on the return to life, liberty, and the pursuit of happiness - Allison, John A. (McGraw-Hill Education, 2015)
Combining practical hands-on strategies with keen insights into public policy and business; author John Allison reveals the fundamental principles he sees as critical to the success of any leader; to all organizations; and to the United States. --
Includes index. - Description based on print version record
Keywords: Business planning; Leadership; BUSINESS & ECONOMICS / Leadership